Avaliação do efeito de punção em lajes lisas de concreto com fibras com a variação do índice de retangularudade - Alves, Vinícius Sandovani da Silva (2017)
The objective of this work is to evaluate the punching in flat slabs of concrete reinforced with different rates of steel fibers and varying the pillar rectangular index in internal column and symmetrical loading. The justification of this research is find in the lack of evaluation of these two variables, simultaneously, in the literature. Moreover, none of these is consider in most normative methods, even that these parameters influence punching resistance. 9 local models of slabs with a dimension of 1800x 1800 mm² and a height of 130 mm were tested, where the amount of added fiber (0, 50 and 60 kg / m³) and the rectangular index (1, 1,5 e 2,03) were varied. The analyzed parameters were the load of rupture, the vertical displacement, deformation of the armature, characteristics and amount of cracks formed. The addition of steel fibers proved effective for increasing puncture resistance, regardless of the rectangular index, leading to the formation of a larger number of cracks and greater vertical displacements after rupture. The rectangular index influenced the puncture resistance and the behavior of the rupture, in which for the index of 1 to 1,5 an increase in puncture resistance occurs, and between 1,5 and 2,03 a decrease occurs. The normative methods in general have been conservative, but considering the large number of variables not considered in the equation, this safety is necessary.